Near seafloor bioluminescence, macrozooplankton and macroparticles at the Mid-Atlantic Ridge. (April 2015) - Craig, Jessica; Youngbluth, Marsh; Jamieson, Alan J.; Priede, Imants G.
Abstract: The benthic boundary layer is a region often perceived to be high in faunal abundance and biomass. In this study, we investigated the distribution of near seafloor bioluminescent zooplankton (BL), macrozooplankton (>1 cm) and macroparticles (>430 μm) at the Northern Mid-Atlantic Ridge at ca. 2500 m depth. At sites south of 52°N, the Charlie Gibbs Fracture Zone, BL density increased weakly towards the seafloor. This trend was driven by small bioluminescent crustaceans, comprising ca. 90% of the total BL density. Macroparticle density was coherent with BL density, exhibiting a small increase towards the seafloor. Appendicularians (animals as well as occupied and discarded houses) were the most abundant macrozooplankton, and the only group to show a significant increase in density towards the seafloor. The absence of pronounced increases in BL and macroparticle density, and no increase in macrozooplankton (except appendicularians), towards the seafloor do not support the conventional view of high concentrations of particulate organic matter and zooplankton biomass in the benthic boundary layer relative to overlying waters. Highlights: Altitude effects of near seafloor (5–100 mab) zooplankton and macroparticles investigated. Density of bioluminescent zooplankton increased weakly towards seafloor. Density of macroparticles (>430 μm) increased weakly towards seafloor. Appendicularians only macrozooplankton group (>1 cm) to increase in density towards seafloor. Results do not support conventional view of enriched benthic boundary layer zooplankton biomass.